STUDENTS WORKSHEET BASED ON ANTI CORRUPTION AND HIGHER ORDER THINKING SKILLS (SWACHOTS): MENGEMBANGKAN PEMBELAJARAN LINGKUNGAN ABAD 21 - Ilmi Zajuli Ichsan; Enin Iriani; Farah Muthi Hermawati; Aryani Kadarwati Dewi (Program Studi Pendidikan Biologi, Fakultas Pendidikan Ilmu Eksakta dan Keolahragaan, IKIP Budi Utomo Malang, 2019)
The topic of river pollution is a learning topic that requires Higher Order Thinking Skills (HOTS). Environmental problems also combine with other problems, one of them is corruption cases in environmental issues is also of particular concern, so the need to instill anti-corruption values. The purpose of this study was to develop Students Worksheet based on Anti Corruption and Higher Order Thinking Skills (SWACHOTS) in environmental learning. The research method used is Research and development based on Borg & Gall (2003). The study was conducted on 12-18 October 2018 in Elementary School 2 of Jatimulya and Junior High School 1 South Tambun, Bekasi. The results showed that the worksheets developed were valid and suitable for environmental learning for Elementary students and Junior High School students with an average score of 3.47. This is because the presentation of SWACHOTS is simple but full of HOTS and anti-corruption values. The conclusion is that developed worksheets are valid and suitable for use in environmental learning.